ANALYSIS OF VISUAL STORYTELLING UTILIZATION ON SOCIAL MEDIA TO ENHANCE THE BRAND IMAGE OF MSMES IN JAMBI CITY - Apriansyah, Willy; Syahmardi yacob; Istiqomah Malinda (Journal of Business Studies and Management Review, 2026)
This study investigates the strategic utilization of visual storytelling on social media platforms to enhance the brand image of micro, small, and medium enterprises (MSMEs) in Jambi City, Indonesia. Utilizing the Stimulus-Organism-Response (SOR) framework as the underlying theoretical foundation, this research examines whether social media engagement (SME) acts as a critical mediating mechanism between visual storytelling and brand image development. A quantitative causal research design was implemented, surveying 100 active social media users in Jambi City who follow and interact with local MSME brands. Data were gathered through a structured online questionnaire and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS4. The empirical results reveal that visual storytelling has a positive and significant direct effect on both brand image and social media engagement. Furthermore, social media engagement exerts a highly significant positive effect on brand image and successfully mediates the relationship between visual storytelling and brand image, exhibiting a partial mediation pattern. Descriptive analysis indicates a critical gap, while Jambi MSMEs suffer from low visual differentiation, they successfully cultivate high brand commitment through relational engagement. These findings suggest that Jambi MSMEs must transition from transactional, hard-selling catalog posts to relational, narrative-driven content to foster active audience interaction and build sustainable brand equity.